The Influence of Interpersonal Conflict and Job Stress on Counterproductive Work Behavior: The Mediating Role of Job Dissatisfaction - Salsabila Fanesa, Olivia; Amali Rivai, Harif; Games, Donard (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of interpersonal conflict and job stress on counterproductive work behavior (CWB), with job dissatisfaction as a mediating variable. The research was conducted among employees of the Perumda Air Minum Office in Padang City, using a probability sampling technique through cluster sampling involving 160 employees. Data were analyzed using the Structural Equation Modeling (SEM) method with the assistance of SmartPLS software. The results indicate that both interpersonal conflict and job stress have a positive and significant effect on counterproductive work behavior. Furthermore, job dissatisfaction also has a positive and significant influence on counterproductive work behavior. Job stress is found to have a direct and significant effect on job dissatisfaction, whereas interpersonal conflict does not significantly affect job dissatisfaction. Job dissatisfaction is proven to mediate the relationship between job stress and counterproductive work behavior, but it does not mediate the relationship between interpersonal conflict and counterproductive work behavior. These findings offer important implications for organizations in managing interpersonal conflict and job stress, with the aim of enhancing job satisfaction and minimizing the emergence of counterproductive behaviors in the workplace.